CULTURAL DIPLOMACY AND GLOBAL CHALLENGES IN G20 INDONESIA 2022 - Nurisnaeny, Poppy Setiawati; Kaprisma, Hendra; Suwedi, Suwedi (UI Scholars Hub, 2024)
Indonesia has been chosen to host the G20 summit in Bali in November 2022. Indonesia has prepared many agendas ahead of the execution of this summit. This preparation concerns the technical implementation of multilateral relations, which have undergone significant changes due to the COVID-19 pandemic. Furthermore, Indonesia needs help hosting the G20 due to the fractured multilateral relations of several G20 member countries caused by the Russia-Ukraine conflict in early 2022. As a result, Indonesia must mediate between the disputing parties to resolve this issue by selecting appropriate communication methods. Cultural diplomacy is one approach. Cultural diplomacy is a non-coercive means of achieving a country's foreign policy goals, specifically through exchanging ideas, values, and culture. Therefore, this research aims to assess the potential strength of Indonesian cultural diplomacy in assisting global economic recovery following the COVID-19 pandemic and encouraging peace in the Russia-Ukraine conflict. Furthermore, this research aims to determine how Indonesia's cultural diplomacy can ensure the continuity of the G20 2022 Indonesia implementation and realization of its agendas. This research aims to solve problems and challenges before and after the G20 2022. This research addresses issues and challenges before and after the G20 2022 meeting. This study employs mixed methods to investigate the relationship or contradiction between qualitative and quantitative variables in research data sources. According to the findings of this study, cultural diplomacy can address the challenges of implementing the G20 2022 and provide projections of possible global conditions after the conference.